Фальсификации или домыслы: опыт выборов в России и в Украине - Мягков, М.; Ордешук, П.; Шакин, Д. (Социология: теория, методы, маркетинг, 2005)
Beginning with the first round of Russia’s 1996 presidential election, through the December 26th third round of Ukraine’s presidential contest, this essay examines the fingerprints of fraud found in election returns aggregated up to the level of Russia’s 2500+ and Ukraine’s 225 rayons. Our objective is to develop methodologies for detecting and measuring fraud that do not rely on eyewitness accounts of electoral irregularities, but which instead can be detected in official data. The evidence we offer as establishing a `crime’ is necessarily circumstantial, but we are reminded that those who `facilitated’ Putin’s 2004 reelection also helped orchestrate the campaign of the Kremlin’s choice of successor to a retiring President Kuchma. If crimes are often solved with reference to a culprit’s modus operandi, then the things we label fingerprints of fraud ought to exist in the official data of both countries. And indeed they do — especially when we compare Putin’s success in 2004 with the patterns of voting that emerged subsequently to favor Viktor Yanukovich in Ukraine. Our secondary objective is to measure the extent of electoral fraud, and here we conclude that Putin’s success at avoiding a second round vote against his communist challenger in 2004 was aided and abetted by upwards of 14.5 million falsified ballots and that between 1.5 and 3.5 million suspicious votes account for Yanukovich’s illfated November 21st “victory”.